2012
DOI: 10.1210/jc.2012-2240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tight Glucose Control with Insulin on the Thyroid Axis of Critically Ill Children and Its Relation with Outcome

Abstract: TGC further accentuated the peripheral inactivation of thyroid hormone. This effect, mimicking a fasting response, statistically explained part of the clinical outcome benefit of TGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
2
26
2
1
Order By: Relevance
“…Our study analyzed 3,933 pediatric patients and intended to expand the trial volume. Both in vitro and in vivo studies revealed that insulin therapy had positive effects of improving organ functions and alleviating inflammatory responses (30)(31)(32). Although tight glycemic control may bring clinical benefits in theory, the pooled analysis of present study did not show obvious survival benefits of TGC compared with CGC in critically ill children.…”
Section: Discussioncontrasting
confidence: 54%
“…Our study analyzed 3,933 pediatric patients and intended to expand the trial volume. Both in vitro and in vivo studies revealed that insulin therapy had positive effects of improving organ functions and alleviating inflammatory responses (30)(31)(32). Although tight glycemic control may bring clinical benefits in theory, the pooled analysis of present study did not show obvious survival benefits of TGC compared with CGC in critically ill children.…”
Section: Discussioncontrasting
confidence: 54%
“…In such clinical studies, it is necessary to measure serum levels of rT3, as well as T4 and T3, to gain more information about the diseases. Even in recent studies measuring rT3 [ 16 , 17 ], measurements were made by RIA, which is the most reliable but very old technique [ 18 ]. However, the number of studies on rT3 has substantially decreased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a multivariate, Cox proportional hazard analysis showed that the further reduction of T 3 and rT 3 accounted for part of the therapy improving patient mortality rates. 82 …”
Section: Pathogenesis Of Ntismentioning
confidence: 99%